The use of virtual reality technologies for the relaxation of pregnant and parturient women: the results of a pilot study - Baryshnikova Valeria Valeriivna (Insight: the psychological dimensions of society, 2022)
Modern methodology of psychological support of pregnantwomen is represented by many effective meansand focus areas, but they mainly concern the prenatalperiod. The aid of a psychologist during childbirthis complicated by objective factors: first of all, there isa lack of trained specialists who can be constantly presentin a delivery room and work in cooperation withdoctors and parturient women. Therefore, the meanswhich can be provided to patients in audio or video formatafter a preliminary briefing arouse interest. In particular,the application of virtual reality technologies,which dive a person into an immersive therapeuticspace, has great prospects. They are actively employedto relieve procedural and acute pain in pediatric, oncological,and burn departments. However, they are stillpoorly introduced into obstetric practice and perinatalpsychology. The purpose of this work is to presentpreliminary results of the implementation of VRrelaxation during contractions in women giving birthfor the first time. Methods. The guided relaxation techniqueis intended for pregnant women; it comprises verbal instructions for deep muscle relaxation, guidedvisualization to enhance salivation and positive suggestionsabout delivery outcome, and 3D backgroundvideo and music. The experimental group included49 participants who used VR glasses with a relaxationprogram during contractions; the control group consistedof 43 women who gave birth traditionally, involvingall other services of the maternity department.Results contain medical records (duration of delivery,anesthesia use, a newborn’s Apgar score) and a surveyof women on their experience 24-48 hours after childbirth.The comparative analysis confirmed a significantdecrease in the use of anesthetic, duration of delivery,intensity and discomfort of labor pain; an increase inthe ability to relax between contractions and betterestimates of the newborn condition. The substantialgrowth of overall satisfaction with labor and the desireto give birth again in the experimental group is crucial.The technology’s effectiveness proves the theoryof the psychogenic origin of labor pain and hencethe relevance of a psychological approach to managingit. The author concluded on the effectiveness of interventionsbased on muscle relaxation of parturientwomen in combination with virtual reality technologies.The presented technology is fully ready-to-use inthe practice of maternity departments.